Business in the cloud what every business needs to know about cloud computing - Hugos, Michael H. (Wiley, 2011)
"A close look at cloud computing's transformational role in business Covering cloud computing from what the business leader needs to know, this book describes how IT can nimbly ramp up revenue initiatives, positively impact business operations and costs, and how this allows business leaders to shed worry about technology so they can focus on their business. It also reveals the cloud's effect on corporate organization structures, the evolution of traditional IT in the global economy, potential benefits and risks of cloud models and most importantly, how the IT function is being rethought by companies today who are making room for the coming tidal wave that is cloud computing. Why IT and business thinking must change to capture the full potential of cloud computing. Topics including emerging cloud solutions, data security, service reliability, the new role of IT and new business organization structures. Other titles by Hugos include: Business Agility: Sustainable Prosperity in a Relentlessly Competitive World and Essentials of Supply Chain Management, 2nd Edition. Practical and timely, this book reveals why it's worth every company's time and effort to exploit cloud computing's potential for their business's survival and success."--